Optimalisasi Penerapan Metode TOPSIS dalam Penentuan Dosen Berprestasi - Purba, Rohan Kristini; Sitorus, Jepri Saprianto; Syahrizal, Muhammad (Journal of Informatics, Electrical and Electronics Engineering, 2023)
The role of lecturers, especially for students, really determines the quality of the students themselves. Therefore, to create a quality future generation, qualified lecturers are also needed. However, currently there are many lecturers who only work as lecturers, but do not meet the criteria for a good lecturer. Giving awards to lecturers who excel is one of the efforts that can be done in order to create work motivation and increase the desire of every lecturer to become a lecturer who has good qualifications. However, the problem is to determine the best lecturers in a university, it will be very difficult if done manually. To make it easier for leaders to assess lecturers who deserve to be called achievers or not, a decision support system (SPK) is needed, where this SPK acts as a support for the leadership's reasons why the leader chooses someone as an outstanding lecturer. Decision Support System (DSS) is a system whose work uses a computer, where this system uses various methods which ultimately produce information in the form of a decision. the method used in this study is the TOPSIS method. The TOPSIS method is one of the DSS methods whose purpose is to produce an alternative with the highest value as an alternative recommendation. The results obtained in this study amounted to 0.5308 on behalf of Mesran as an alternative recommendation.